Characterization of a Monoclonal Antibody, D73H, that Maps to a Highly Conserved Region on Fibrinogen Bβ Chain - Rybarczyk, B. J.; Pereira, M.; Simpson-Haidaris, P. J. (Thrombosis and Haemostasis, 2000)
The primary structure of fibrinogen is highly conserved across species, yet often times monoclonal antibodies produced against the fibrinogen of one species will not crossreact with the fibrinogen of another. Herein, we describe the production and characterization of murine MAb, D73H, raised against human fibrinogen. D73H crossreacts with a highly conserved epitope on the Bβ chain of fibrinogen from human, rat, bovine, guinea pig, and mouse. Western blotting revealed that D73H reacted with the Bβ chain of plasmin fragment D, localizing its epitope to Bβ134-461. A 7 kDa band was identified by D73H in Western blots of reduced fibrinogen CNBr-fragments. N-terminal sequencing mapped this fragment to Bβ243-253, further localizing the epitope to Bβ243-305. In silico analysis indicated that Bβ243-305 is predominantly hydrophilic, and surface probability prediction indicated three potential antigenic determinants corresponding to Bβ252-258, Bβ262-269, and Bβ279-286. Further in silico analysis of the crystal structure of fibrinogen fragment D-D indicated that Bβ262-269 (FGRKWDPY) is predominantly α-helical and located on the surface of the molecule adjacent to a bend imposed in the β chain at residue 260, which is near the junction between the rigid coiled-coil domain and the globular C-terminus. A synthetic peptide corresponding to Bβ261-272 competitively inhibited the binding of D73H to the Bβ chain of denatured intact fibrinogen and reduced and denatured Bβ chain in Western blots, experimentally proving the validity of these predictive algorithms. Together these data indicate that, although plasmin resistant, Bβ chain residues Bβ261-272 comprising the D73H epitope are highly conserved across species, surface exposed, and immunogenic.
Keywords: Crystal structure; in silico analysis; epitope mapping; cyanogen bromide; plasmin